PELATIHAN PRESENTASI MENGGUNAKAN MICROSOFT POWERPOINT DI SMP IBRAHIMY 3 SUKOREJO SITUBONDO - Elvina Eldiavani; Meliana Khamisah; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
Presentations are the ability to transfer knowledge effectively. Microsoft PowerPoint is a robust and reliable presentation software. The skill of presenting information visually and engagingly is no longer just a supplementary ability; it's key to developing students' critical thinking, creativity, and communication effectiveness.However, at SMP Ibrahimy 3, a significant gap has been identified in female students' mastery of the PowerPoint application. Varying levels of understanding and limited access to computers result in suboptimal, less interactive presentations that fail to convey information effectively. This situation directly hinders the students' academic potential in various learning activities, from project assignments to group discussions.Therefore, efforts to improve proficiency in using Microsoft PowerPoint are crucial to equip students with relevant and essential digital skills in the current era.